Patient‐derived pancreatic tumour organoid implantation establishes novel pre‐cachexia mouse models - Merel R. Aberle; Rianne D.W. Vaes; Wouter R.P.H. van deWorp; Ludwig J. Dubois; Natasja G. Lieuwes; Rianne Biemans; Ramon C.J. Langen; Frederik‐Jan vanSchooten; Ronald M. vanDam; Steven W.M. Olde Damink; Sander S. Rensen (JCSM Rapid Communications, 2023)
Abstract Background The poor survival of pancreatic cancer patients is largely attributable to cachexia, a syndrome of severe weight and muscle loss. To investigate the aetiology of cancer cachexia, preclinical models that closely recapitulate the human disease process are essential. Patient derived tumour organoids are promising novel cancer models, but their ability to induce cachexia in mice has not been investigated. We developed two pancreatic tumour organoid‐based mouse models and demonstrate their potential for cancer cachexia research. Methods Two patients with pancreatic cancer, from whom tumour organoid cultures were previously established, were selected based on their cachexia phenotype. Patient 09 was characterized as cachectic according to the international consensus definition of cancer cachexia, whereas patient 12 was classified as non‐cachectic. Organoid cultures PANCO‐09b and PANCO‐12a in basement membrane extract (BME) were injected subcutaneously into the flanks of 9‐weeks old NMRI‐Foxn1nu mice (n = 8/group). A control group was injected with BME only (n = 4). Body weight was monitored every 2–3 days for 38 days. Hind limb muscle wet and dry weights were measured. Adipocyte size in inguinal white adipose tissue was measured using haematoxylin and eosin‐stained sections. Expression of genes associated with cancer cachexia in muscle and liver tissue was analysed using qPCR. Results Engraftment of tumour organoids was successful in 87.5% of PANCO‐09b implanted mice and in 50% of PANCO‐12a mice, with similar average tumour weights at endpoint (34.4 ± 25.1 mg vs. 32.8 ± 40.2 mg, respectively, P = 0.450). All groups initially gained weight, but PANCO‐12a implanted mice progressively lost an average body weight of 1.7 ± 0.8 g from day 28 onwards. PANCO‐12a‐implanted mice gained significantly less weight from baseline than controls (0.7 ± 0.6 g, P = 0.027). Overall body weight gain of PANCO‐09b mice was also lower but not significantly different from controls (2.0 ± 1.2 g vs. 2.9 ± 1.6 g, P = 0.961). Wet weights of hind leg muscles were negatively correlated with tumour weight but did not differ between groups. Adipocytes of PANCO‐12a implanted mice were smaller compared to SHAM as well as PANCO09b mice (P < 0.0001), indicative of white adipose tissue wasting. Conclusions Implantation of human pancreatic tumour organoids into mice negatively affects their body weight, but does not recapitulate body weight loss of donor patients. The reduced adipocyte size and inverse correlation between tumour weights and muscle weights in these mice are consistent with early‐stage cachexia or pre‐cachexia. This study shows that implantation of tumour organoids into mice provides a valuable model to investigate the processes underlying the heterogeneous presentation of cancer cachexia.